The relationship between internet usage and subjective wellbeing among youths in Malaysia - Omar, Siti Zobidah; Fadzil, Mohd. Fauzi; Bolong, Jusang (Human Resource Management Academic Research Society, 2019)
The objective for this study is to examine the relationship between internet usage and subjective wellbeing (using a Scale of Positive and Negative Experience or SPANE) among multiracial youths in Malaysia. This study attempts to close the gap between practice and research that focuses on internet usage and Malaysian youth wellbeing. The study uses a quantitative approach (cross sectional survey) whereby 400 youths across four zones in Malaysia were selected as respondents. Based on the aim of this study, it was found that all three factors studied which is psychology and family relationship wellbeing; leisure and health wellbeing and; socio-economic wellbeing are significantly related to positive feelings but none of them yield significant results with negative feelings. The study stresses on the need for parents to advocate their children on the proper use of internet, especially youths in the age of 15 to 25.